A TEM Heart Transplant: The Development of a User Adjustable Pole-piece (UAP) - McBean, Patrick (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
Transmission Electron Microscopes (TEMs) have massively accelerated progress in many areas of science, particularly biology and material science. Atomic-scale resolution was achieved soon after the invention of the TEM, and a plethora of spectroscopic analysis devices are now available for the platform to widen its capabilities. A major choice that must be made when purchasing a microscope is the size of the pole-piece gap where the sample is inserted. This decision is made during the competitive tendering process, and the choice will remain installed for the rest of the TEM's lifetime; approximately 15 years. Opting for a smaller gap results in reduced aberrations and thus better resolution, while opting for a larger gap enables better support for analytical techniques. These include a better tilt range of the sample, more space to fit a wide range of in-situ, cryogenic, or tomographic holders, or to move EDX (energy-dispersive X-ray spectroscopy) detectors as close to the sample as possible in order to improve collection efficiency. Presently both a large and small gap cannot be selected simultaneously, so a compromise between high-resolution capability, and analytical capabilities is inevitable. However, we suggest a User Adjustable Pole-piece (UAP), where the pole-piece gap can be adjusted by the microscope operator themselves from outside of the column, requiring no disassembly and crucially, remaining under vacuum in the column. A TEM column equipped with a UAP would have greatly improved functionality, allowing it to support both ultra-high resolution work and analytical techniques within just one instrument, something not previously possible. This thesis will discuss the background theory required to build such a pole-piece, and examine previous attempts to do so from the literature. Magnetic and optical modelling of the performance of such a lens with various geometries will be analysed, along with fabrication methods for prototypes and the final unit. The design choices stemming from these simulations and prototypes will be showcased, culminating in the final design which was built here in Ireland and installed an in-service TEM for testing.
APPROVED
Keywords: Transmission Electron Microscopy; Electron Optics; Pole-piece Gap; Objective Lens